Simultaneous strain measurements of knee ligaments - Ng, Eugene Zhong Hui (2015)
Ligaments injuries are commonly found among athletes and they occur due to adverse combinations of internal and external forces and torques; the most common injury being the anterior cruciate ligament (ACL) tear. The purposes of this study are: firstly, to design and modify an existing custom-designed knee fixture which allows multiple degree of freedom of the knee, and secondly, to assess the strain responses of all ligaments simultaneously under various loading conditions. Computer-aided design software, Solidworks, was used to simulate the new design and fabrication was done in Nanyang Technological University (NTU) manufacturing laboratory. Porcine specimen was used to conduct preliminary test to evaluate the functionality of the newly-designed fixture. Experiment was then conducted on cadaveric knee. DVRT (MicroStrain Inc, Williston, Vermont), with a linear range of ± 3 mm was calibrated and implanted into the ligaments by its barbed prongs. Due to limitations from the transducer, only the strain values of the medial collateral ligament (MCL) and lateral collateral ligament (LCL) were recorded. Two series of tests were performed: (1) 2.kg, 5kg and 7.5kg anterior and posterior directed shear load at various flexion angle, (2) 5°, 10° and 15° internal and external tibial rotations at various flexion angle. Both tests were conducted at flexion angles of 0°, 30°, 60° and 90°. Both MCL and LCL were found to be tightest at full extension and relaxed as the knee went into flexion. Strain values of MCL were consistent with past literature as it resisted external tibial axial rotation while being compressed under internal tibial axial rotation. Owing to the inconsistent strain results from LCL, it was hypothesised that LCL is a secondary stabiliser to both internal and external rotation [46]. Future work is required to obtain the strain responses of ACL and posterior cruciate ligament (PCL), along with MCL and LCL simultaneously under combined external loading conditions to understand their interactions in providing total stability in the knee joint.